SUMFOLK database - Demographic Data Base - Centre for Demographic and Ageing Research, Demographic Data Base, Umeå University (Umeå University, 2025)
The SUMFOLK database contains a compilation of the aggregated population reports for the years 1895-1930 made by Gunnar Myrdal's research group during the 1930s. They are based on information sent to Statistics Sweden (SCB) by the country's ministers. There is information on migration, population and the number of births and deaths at parish level. Myrdal's research group extracted certain information from the original forms to their own excerpt forms. These excerpts have been registered by Demographic Data Base (DDB) and are available in the SUMFOLK database.

Den summariska folkmängdsdatabasen innehåller en sammanställning av de summariska folkmängdsredogörelser för åren 1895-1930 som gjordes av Gunnar Myrdals forskargrupp under 1930-talet. De bygger på information som skickades in till Statistiska centralbyrån (SCB) från landets präster. Det finns information om migration, folkmängd och antalet födda och döda på församlingsnivå.

Myrdals forskargrupp excerperade viss information från originalblanketter, på egna excerperingsformulär. Det är dessa excerpter som har inregistrerats av Demografiska databasen (DDB) och som finns tillgängliga via den summariska folkmängdsdatabasen.
Summariska folkmängdsdatabasen - Demografiska databasen
Keywords: immigration; invandring; emigration; utvandring; demographic statistics; befolkningsstatistik; migration (demography); migration (människor); Deaths; Döda; Immigrated; Inflyttade; Emigrated; Emigrerade; Births; Födda; DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); Morbidity and mortality; Morbiditet och mortalitet; Censuses; Folkräkningar; Migration; Migration; Social welfare policy; Välfärdspolitik; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap; History; Historia